HUMAN RIGHTS PERSPECTIVES ON ISSUES IN THE IMPLEMENTATION OF ISLAMIC CRIMINAL LAW IN MALAYSIA - Mohd Hisham Mohd Kamal (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2019)
This paper discusses the implementation of Islamic Criminal Law in Malaysia from the human rights perspectives. It looks at Shariah Criminal Offences Enactments and Sharia Criminal Procedure Enactments of States forming the Federation, and deals with the issues of the victimless Sharia offences of khalwat, fornication and drinking intoxicants, determining whether such criminalization is compatible with human rights. Discussion also deals with the issues of sanction and procedures, in finding out the extent to which Malaysia is complying with its International Human Rights Law obligations, if there is any. This paper finds that the Sharia statutory provisions are compatible with the human rights concept. In some extends, Shariah law can explore law uncertainty, because referring to the God’s law instead of the nature law. Most of human rights concept have come from the philosophy of the nature law. Thus, the approach of the nature law will always change depending of time period. However, Sharia law needs to improve the training of religious enforcement officers on how to carry out their duties. Abstrak: Artikel ini membahas penerapan Hukum Pidana Islam di Malaysia berdasarkan perspektif hak asasi manusia (HAM). Penelitian ini menyelidiki penegakan pelanggaran syariah dan penegakan hukum pidana syariah pada Negara Federasi, yang berkaitan dengan isu-isu pelanggaran syariah khalwat, percabulan dan minum minuman keras, serta menentukan apakah kriminalisasi tersebut sesuai dengan hak asasi manusia. Artikel ini juga membahas masalah sanksi dan prosedur untuk mengetahui sejauh mana Malaysia mematuhi kewajiban hukum hak asasi manusia internasional, jika ada. Penelitian ini menemukan bahwa ketentuan hukum syariah sesuai dengan konsep hak asasi manusia. Dalam beberapa hal, hukum syariah dapat mengeksplorasi keraguan hukum, karena merujuk pada hukum Tuhan, bukan hukum alam. Sebagian besar konsep HAM berasal dari filosofi hukum alam, oleh karena itu, pendekatan hukum alam akan selalu berubah seiring waktu. Namun, hukum Syariah perlu melatih aparat penegak hukumnya berkaitan dengan bagaimana mereka melaksanakan tugas. Kata kunci: Perspektif Hak Asasi Manusia, Hukum Pidana Islam, Hak Asasi Manusia dalam Islam